STRATEGI PENGEMBANGAN USAHA TAHU DI KECAMATAN SEI BINGAI SUMATERA UTARA (Studi Kasus : Usaha Tahu Bu Murni) - Ryan Irwansyah; Siti Balqies Indra; Supristiwendi, Supristiwendi (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
used in this research is SWOT and QSPM analysis. The results of this study indicate that there are four alternative strategies obtained from the SWOT analysis, namely (SO1) Improve strategic facilities to gain wide market reach. (SO2) maintain product quality to get high product demand, (WO1) try to use digital marketing to improve product marketing in order to get a wide market reach and high demand. (WO2) establish business groups and legal entities to obtain equipment assistance from the government for business development, (ST1) maintain prices when the price of raw materials is high. (ST2) maintains sufficient availability of raw materials to keep up with changing consumer demands. (WT1) manages the financial statements of Mrs. Murni's tofu business to purchase more modern equipment in order to compete in the modern market trends that are developing. (WT2) makes product variations so that the product is not easily imitated. Based on the QSPM analysis, the priority of the main strategy in this research is to increase the strategic place of business to get a wide market reach